Humoral immune response against melanoma antigens induced by vaccination with cytokine gene-modified autologous tumor cells - Ehlken, Hanno; Schadendorf, Dirk; Eichmüller, Stefan B. (International journal of cancer, 2004)
Although the existence of a humoral response against tumor-associated antigens is well appreciated, a systematic analysis of its possible induction by the tumor remains missing. We compared the specific IgG response of Stage IV melanoma patients during vaccination. Patients had been treated within 2 clinical trials with autologous tumor cells gene-modified for IL-7 or IL-12. A panel of 27 tumor-associated antigens (HD-MM-01 to HD-MM-27) was isolated by a SEREX screening of a testis cDNA library using a pool of 5 sera from patients after vaccination. All antigens were retested with individual sera of 12 patients both pre- and post-vaccination. A serological response was induced during vaccination against 18 antigens. Remarkably, induction was detected only in patients included in the screening pool. The low overlap between sero-reactivity of the 12 patients suggested a very individualized immunological reaction. Two of 5 sera included in the screening pool exhibited a high frequency of induced humoral responses. The same patients had been shown to have a high Karnovsky index and had generated lytic cytotoxic T cells against the tumor. Besides 2 known cancer-germline genes (SCP-1 and PLU-1), the other isolated antigens were expressed in a non-tumor-specific fashion as analyzed by virtual Northern blot or RT-PCR. The properties of homologues to several of the identified tumor-antigens, especially PLU-1, SCP-1, DNEL2, CLOCK, and PIASx-α, suggest further investigation of their possible function in malignant melanoma. We conclude that a strong humoral response against tumor-associated antigens is inducible by tumor cells and that this response is very individual.
First published: 27 October 2003
Gesehen am 25.11.2020